Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1432-1327.1998.2580686.x
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterisation of lysozyme binding to LPS Re and lipid A

Abstract: The binding of lysozyme to bacterial deep rough mutant lipopolysaccharide (LPS) Re and to its lipid moiety lipid A, the 'endotoxic principle' of LPS, was investigated using biophysical techniques. The β↔ A gel to liquid crystalline phase transition, the nature of the functional groups of the endotoxins, the secondary structure of lysozyme, and competition with polymyxin B were studied by Fourier-transform infrared spectroscopy (FTIR); the supramolecular aggregate structure of the endotoxins was determined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 28 publications
6
34
1
Order By: Relevance
“…It was previously found that the conical shape of the lipid A part of the LPS molecule is necessary to exhibit endotoxic activity in a biological system (16,38). This lamellarization of the endotoxin aggregates has also been observed for other proteins and polypeptides that inhibit the cell stimulation activity of LPS, such as lactoferrin (14), high-density lipoprotein (13), lysozyme (15), and polymyxin B (17). The interaction of LPS with LBP and CD14 may thus be directly influenced as a consequence of this structural change.…”
Section: Discussionmentioning
confidence: 75%
“…It was previously found that the conical shape of the lipid A part of the LPS molecule is necessary to exhibit endotoxic activity in a biological system (16,38). This lamellarization of the endotoxin aggregates has also been observed for other proteins and polypeptides that inhibit the cell stimulation activity of LPS, such as lactoferrin (14), high-density lipoprotein (13), lysozyme (15), and polymyxin B (17). The interaction of LPS with LBP and CD14 may thus be directly influenced as a consequence of this structural change.…”
Section: Discussionmentioning
confidence: 75%
“…This is particularly the case with polymyxin B, lysozyme, the limulus anti-LPS factor, and with the two structurally related mammalian proteins that share high affinity binding to LPS: bactericidal/permeability-increasing protein and lipopolysaccharide-binding protein. For example, polymyxin B and lysozyme bind electrostatically to the phosphate groups of lipid A, as shown by analysis of phosphate vibration (42). Concerning LPS-binding protein and bactericidal/permeability-increasing protein, the interactions of these proteins with LPS seems to be a complex multisystem process involving, on one hand, the lipid-binding pockets of these molecules (which can accommodate the apolar moiety of LPS but with little specificity) and, on the other hand, positively charged groups (between residues 90 and 103) (43) leading to electrostatic interactions with phosphorylated sugar groups of LPS (44).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand the interaction of proteins with endotoxins as it led to divergent effects on LPSinduced responses (Tesh and Morrison, 1988; Roth and Kaca, 1994; Machnicki et al, 1993;Yu and Wright 1996;Brandenburg et al, 1998), which serve as a basis for many clinical and therapeutic applications. Inspired by this, we report a simple but useful advance in the design of an experimental system that enables a quick, quantitative, and label-free detection of LPSbiomolecular interactions (Das et al, 2015).…”
Section: A Simple Quantitative Methods To Study Proteinlipid Interactimentioning
confidence: 99%